MORALITY: THE NEED OF TODAY’S EDUCATION - Henny Yulia (Universitas Muhammadiyah Kotabumi, 2018)
Character is very important aspect of human being. Having good character will contribute students to have good personality. Both parent and teacher have responsibility to inculcate the character to the children since they are elder person who usually interact with them. Morality is part of character which is very needed today. The fact that some children loose their respect to the parent, teachers, and friends is a signal that there is a degradation of students character. School as places where students spend most of their time must give good contribution to students characters. The importance of teaching morality and how to insert morality in school become the topic of this paper. It is hoped that by having good morality, indonesian education will become better and better which automatically makes the quality of indonesian education become highly improved.